Functional Analysis of the Nitrogen Metabolite Repression Regulator Gene nmrA in Aspergillus flavus - Han, Xiaoyun; Qiu, Mengguang; Wang, Bin; Yin, Wen-Bing; Nie, Xinyi; Qin, Qiuping; Ren, Silin; Yang, Kunlong; Zhang, Feng; Zhuang, Zhenhong; Wang, Shihua (Frontiers in Microbiology, 2016)
In Aspergillus nidulans, the nitrogen metabolite repression regulator NmrA plays a major role in regulating the activity of the GATA transcription factor AreA during nitrogen metabolism. However, the function of nmrA in Aspergillus flavus has not been previously studied. Here, we report the identification and functional analysis of nmrA in A. flavus. Our work showed that the amino acid sequences of NmrA are highly conserved among Aspergillus species and that A. flavus NmrA protein contains a canonical Rossmann fold motif. Deletion of nmrA slowed the growth of A. flavus but significantly increased conidiation and sclerotia production. Moreover, seed infection experiments indicated that nmrA is required for the invasive virulence of A. flavus. In addition, the ΔnmrA mutant showed increased sensitivity to rapamycin and methyl methanesulfonate, suggesting that nmrA could be responsive to target of rapamycin signaling and DNA damage. Furthermore, quantitative real-time reverse transcription polymerase chain reaction analysis suggested that nmrA might interact with other nitrogen regulatory and catabolic genes. Our study provides a better understanding of nitrogen metabolite repression and the nitrogen metabolism network in fungi.